Integrated systems‐genetic analyses reveal a network target for delaying glioma progression. Issue 9 (17th August 2019) - Laaniste, Liisi; Srivastava, Prashant K.; Stylianou, Julianna; Syed, Nelofer; Cases‐Cunillera, Silvia; Shkura, Kirill; Zeng, Qingyu; Rackham, Owen J. L.; Langley, Sarah R.; Delahaye-Duriez, Andree; O'Neill, Kevin; Williams, Matthew; et al.
Abstract: Objective: To identify a convergent, multitarget proliferation characteristic for astrocytoma transformation that could be targeted for therapy discovery. Methods: Using an integrated functional genomics approach, we prioritized networks associated with astrocytoma progression using the following criteria: differential co‐expression between grade II and grade III IDH1 ‐mutated and 1p/19q euploid astrocytomas, preferential enrichment for genetic risk to cancer, association with patient survival and sample‐level genomic features. Drugs targeting the identified multitarget network characteristic for astrocytoma transformation were computationally predicted using drug transcriptional perturbation data and validated using primary human astrocytoma cells. Results: A single network, M2, consisting of 177 genes, was associated with glioma progression on the basis of the above criteria. Functionally, M2 encoded physically interacting proteins regulating cell cycle processes and analysis of genome‐wide gene‐regulatory interactions using mutual information and DNA–protein interactions revealed the known regulators of cell cycle processes FoxM1, B‐Myb, and E2F2 as key regulators of M2. These results suggest functional disruption of M2 via gene mutation or altered expression as a convergent pathway regulating astrocytoma transformation. By considering M2 as a multitarget drug target regulating astrocytoma transformation, we identified several drugs that are predicted to restore M2 expression in anaplastic astrocytoma toward its low‐grade profile and of these, we validated the known antiproliferative drug resveratrol as down‐regulating multiple nodes of M2 including at nanomolar concentrations achievable in human cerebrospinal fluid by oral dosing. Interpretation: Our results identify M2 as a multitarget network characteristic for astrocytoma progression and encourage M2‐based drug screening to identify new compounds for preventing glioma transformation.